2015
DOI: 10.3141/2485-01
|View full text |Cite
|
Sign up to set email alerts
|

Speed Control Method for Highway Tunnel Safety Based on Visual Illusion

Abstract: The low luminance and the monotony of highway tunnels are likely to cause drivers to experience a visual illusion while driving. Drivers tend to underestimate their speed and thus are exposed to a higher risk of relatively severe traffic accidents. Finding a low-cost way to reduce this visual illusion and to improve traffic safety is a challenge for current highway tunnel operations. High-frequency visual information can make a driver overestimate speed; low-frequency visual information may induce a driver to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…It appears unlikely that drivers put more effort into the yellow or blue sidewall markings in dark tunnels. Previous research found that the luminance and lightness can affect speed perception . Consequently, the hue, saturation, and lightness may have combined effects on speed perception.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It appears unlikely that drivers put more effort into the yellow or blue sidewall markings in dark tunnels. Previous research found that the luminance and lightness can affect speed perception . Consequently, the hue, saturation, and lightness may have combined effects on speed perception.…”
Section: Discussionmentioning
confidence: 97%
“…Experiments were carried out in this study to examine the precision of the simulation test compared with the field test (both are common sections of highways). Wan et al [28] analyzed the difference between the real speed in a low-luminance tunnel and the perceived speed of the tunnel model in a driving simulation, and the difference was about 30%. If the low-luminance tunnel is chosen as the standard stimulus, then it would be difficult to meet the degree of accuracy requirements.…”
Section: Precision Checksmentioning
confidence: 99%
“…There is a high risk associated with real vehicle testing in highway tunnels as well as a dependency on tunnel sidewall marking installation, which would affect traffic flow and management while increasing testing expenses. In order to overcome these difficulties and avoid the poor reproducibility inherent in that method, this study used Autodesk 3ds Max® (https://www.autodesk.com/products/3dsmax/overview) to establish a highway tunnel driving simulation model (Wan et al 2015). Autodesk 3ds Max® is a 3D computer graphics program, which can be used to making 3D animations, models and images.…”
Section: Methodsmentioning
confidence: 99%
“…The test was conducted in the Wuhan University of Technology, Intelligent Transport System, High Definition (WUTITS-HD), an advanced driving simulator produced by Wuhan University of Technology ( Figure 1) (Wan et al 2015). The driving simulator used in the experimentation is a full scale, dynamic simulator, with steering wheel with force feedback.…”
Section: Driving Simulatormentioning
confidence: 99%
See 1 more Smart Citation